A STUDY ON FINANCIAL ASSISTING IMPLEMENTS IN HANDLOOM INDUSTRY - T. Monisha; R. Sivanesan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India is a developing nation with a significant portion of its population residing in rural areas. In rural regions, agriculture are the mainstay of employment. After agriculture, the handloom industry is one of the largest employers in rural areas, providing significant livelihood opportunities. The handloom sector is an essence example of a decentralized and traditional industry, deeply rooted in India’s cultural heritage. Even though employing a vast workforce, the handloom sector often struggles to achieve economic stability. The weavers are facing many financial problem in this work such as capital shortage, high price of raw materials, delay getting wages, limited access to credit, high Interest rates on loans, Limited market access, inability to invest in new designs and dependence on informal credit source. The weavers are unaware about their various financial assistance. So the present study expresses the financial assisting implements in the handloom industry.